A changing climate for business : business planning for the impacts of climate change - Metcalfe, G; Jenkinson, K; Johnstone, K (UKCIP, 2009)
The weather already significantly affects economic activity. As the climate changes, all sectors of UK business will be faced with preparing for a range of new threats and opportunities. This report presents guidance for business and business support organisations, based on UKCIP’s experience of working with business. Section 1 provides key messages and suggestions for initial actions. The rest of the report provides more information about future climate and techniques for understanding and assessing likely threats and opportunities.